The study of the soil texture effect, nutrition, and pH on the production of Artemisinin in Artemisia annua L. (Asteraceae) - H Lari yazdi; RA Khavarinejad; AH Roustaian; A Goudarzi (Institue of Medicinal Plants, ACECR, 2002)
Artemisinin is an antimalarial compound that is naturally found in Artemisia annua L. (Asteraceae). The effect of some factors such as soil texture, nutrition, and pH were studied on the production of Artemisinin in Artemisia annua L. The highest amount of Artemisinin (0.065%) was found in the sample which was potted in sandy-loam and the lowest amount (0.043%) ed to the sample grew in silt-loam soils. The nutrient solution without P presented the lowest amount of Artemisinin and lowest decrease in Artemisinin production was preformed in solution without Mg comparing with other solutions. The nutrient solution with 210 mgl-1 N presented the maximum amount of Artemisinin (0.052%). The maximum amount of Artemisinin was presented in pH= 6-7 (0.064% in pH= 6.5).